Effect of Shade on Xylem Development of Moringa oleifera (Alrawag) Seedlings (University of Khartoum Journal of Agricultural Sciences, 2023)
This study investigated the effect of shade as a moderator oflight intensity and temperature on xylem development of seedlings ofMoringa oleifera. Three levels of shade were used: high shade, mediumshade and no shade. Four sequential harvests were carried out monthly forthe seedlings starting from four weeks after seed sowing. Cross sectionswere prepared from the lower and middle parts of the stems at eachharvest and vessel volume fraction, vessel diameters, number of vesselsand volume fraction of lignified cells were measured. The results showedthat the effect of shade was significant on the anatomical variables.Generally, the values of the anatomical variables of the stem wood of theseedlings decreased with increased shade level. The findings indicate theimportance of shade to M. oleifera seedling development and that itshould be considered in nursery conditions.